2020
DOI: 10.1097/md.0000000000020939
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the rehabilitation of intensive care unit acquired weakness

Abstract: Introduction: Traditional physiotherapy is currently the best approach to manage patients with intensive care unit acquired weakness (ICUAW). We report on a patient with ICUAW, who was provided with an intensive, in-patient regimen, that is, conventional plus robot-assisted physiotherapy. Aim of this case study was to assess the efficacy of a combined approach (conventional plus robot-assisted physiotherapy), on muscle strength, overall mobility, and disability burden in a patient with ICUAW in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…Consoante Chillura et al, (2020), o tratamento que se utiliza da reabilitação precoce na UTI consiste, principalmente, em mobilização, em estimulação elétrica muscular e em fisioterapia convencional, a qual foi relatada como capaz de melhorar o resultado do paciente, além de ser o melhor tratamento para pacientes com FAUTI, pois ele é capaz conter o avanço da incapacidade.…”
Section: Discussionunclassified
“…Consoante Chillura et al, (2020), o tratamento que se utiliza da reabilitação precoce na UTI consiste, principalmente, em mobilização, em estimulação elétrica muscular e em fisioterapia convencional, a qual foi relatada como capaz de melhorar o resultado do paciente, além de ser o melhor tratamento para pacientes com FAUTI, pois ele é capaz conter o avanço da incapacidade.…”
Section: Discussionunclassified
“…This can have a positive impact on sleep quality [ 31 ], development of delirium [ 42 ], and cognitive impairment [ 45 ]. Six studies have also shown that VR can help during rehabilitation [ 47 , 48 , 57 , 58 , 73 , 74 ]. The application led to an increase in activity and was well tolerated by the patient without the occurrence of adverse events such as falls.…”
Section: Discussionmentioning
confidence: 99%
“…They have been proposed as a strategy to facilitate out-of-bed mobilisation for ICU patients [143]. However, proposed exoskeleton devices remain in their infancy for the critically ill population, with limited studies investigating back-support exoskeletons worn by staff to reduce physical burden during patient handling [144], body weight supported robotic gait retraining (Lokomat) [145], robotic mobilisation devices such as the VEMOTION ® that can be attached to a specific patient bed [146,147], and upper limb robotic devices such as the Armeo © Spring [145]. Whilst currently proposed as useful adjunctive therapies for traditional ET, future research is required to determine feasibility, safety, and benefits of these devices.…”
Section: Emerging Technologiesmentioning
confidence: 99%